Investigation of attitudes and classroom practices of educators and learners in relation to English as the medium of instruction at four primary schools in Rwanda - Habyarimana, Hilaire (My University, 2015)
This study was conducted in the context of the 2009 language in education policy in Rwanda. It has a three-fold focus. Firstly, it investigates the attitudes of educators and learners towards English as medium of instruction (MoI) in four Grade Six primary schools in Rwanda. Secondly, it explores challenges posed by using a foreign instructional language in the classroom, and finally it investigates the strategies undertaken to address the identified challenges. The data was collected and analysed using the mixed method approach, and the study utilised triangulation as a research design. Data collection was done by means of questionnaires, audio-recordings, and observations of lessons and interviews. A total of 185 learners, 24 teachers, four principals, and two deputy principals participated in the study. The findings revealed that educators and learners have positive attitudes towards English as MoI underpinned by integrative and instrumental motivation. The role of government propaganda for English and the participants’ beliefs in investment in a foreign language were the main motivators. However, it was found that unreserved enthusiasm for English is not enough to make it the effective instructional language in Rwanda. This was evident in the challenges posed by the fact that English is simultaneously being learnt and being used as MoI. The study revealed many challenges in comprehension, speaking, reading, writing, and language structure. Using Vygotsky’s (1978) sociocultural theory as a theoretical framework, it was found that insufficient expertise in English inhibits the types of classroom interactions that are key to learning. Finally, the study identified different strategies used for learning in English in the four primary schools of Rwanda. The main strategy was switching between English, the instructional language, and Kinyarwanda, the participants’ mother tongue (MT). It was found that the use of Kinyarwanda plays an important meditational role for content learning and knowledge building. The study concludes by providing a number of recommendations that could be useful to Rwandan education stakeholders regarding what is happening in the English medium classrooms. The study positions itself among many others of the same nature and finds its value in sensitising the policy planners on the implications of learning a language while using it as the MoI.
THESIS Submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Applied English Language Studies, Faculty of Humanities, School of Education, University of the Witwatersrand, Johannesburg, South Africa